Azithromycin for sarcoidosis cough: an open-label exploratory clinical trial. Issue 4 (10th November 2020) - Fraser, Simon D.; Thackray-Nocera, Susannah; Shepherd, Marica; Flockton, Rachel; Wright, Caroline; Sheedy, Wayne; Brindle, Kayleigh; Morice, Alyn H.; Kaye, Paul M.; Crooks, Michael G.; Hart, Simon P.
Background: Chronic cough is a distressing symptom for many people with pulmonary sarcoidosis. Continuous treatment with a macrolide antibiotic may improve cough. We aimed to assess the potential efficacy of azithromycin in patients with sarcoidosis and self-reported cough. Methods: We conducted a noncontrolled, open-label clinical trial of azithromycin 250 mg once daily for 3 months in patients with pulmonary sarcoidosis who reported a chronic cough. The primary outcome was number of coughs in 24 h. Secondary outcomes were cough visual analogue scales and quality of life measured using the Leicester Cough Questionnaire and King's Sarcoidosis Questionnaire. Safety outcomes included QTc interval on ECG. Measurements were made at baseline and after 1 and 3 months of treatment. Results: All 21 patients were white, median age 57 years, 9 males, 12 females, median 3 years since diagnosis. Five were taking oral corticosteroids and none were taking other immunosuppressants. Twenty patients completed the trial. The median (range) number of coughs in 24 h was 228 (43–1950) at baseline, 122 (20–704) at 1 month, and 81 (16–414) at 3 months (p=0.002, Friedman's test). The median reduction in cough count at 3 months was 49.6%. There were improvements in all patient-reported outcomes. Azithromycin was well tolerated. Conclusion: In a noncontrolled open-label trial in people with sarcoidosis who reported a chronic cough, 3 months of treatment with azithromycin led to improvements in a range of cough metrics. Azithromycin should be tested as a treatment for sarcoidosis cough in a randomised placebo-controlled trial. In a noncontrolled open-label trial in people with sarcoidosis who reported a chronic cough, 3 months of treatment with azithromycin led to improvements in a range of cough metrics https://bit.ly/2FB5tfq